Kajian Etnolinguistik Pembelajaran Bahasa Indonesia bagi Penutur Asing (BIPA) Lintas Budaya Eropa - Sahrul Romadhon; Bambang Yulianto; Mulyono Mulyono; Djodjok Soepardjo; Agusniar Dian Savitri (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
This research stems from the need for Bahasa Indonesia bagi Penutur Asing (BIPA), which not only emphasizes linguistic aspects but also promotes cultural integration in a cross-cultural context, particularly in Europe. This study aims to analyze the integration of Indonesian linguistic and cultural aspects in the process of cross-cultural BIPA learning in Europe, as well as how the cultural elements of each learner contribute to their language skills outcomes. The research method employed is a descriptive qualitative approach, with data collection primarily conducted through online classroom observation and analysis of learners' language skills. The results show that there is integration of each learner's culture in the results of their language skills. In speaking and writing skills, learners not only use Indonesian vocabulary and language structures, but also adapt expressions, communication styles, and cultural values from their home countries to the Indonesian context. In reading and listening skills, learners are able to interpret cultural meanings in texts and audio, while comparing them with their own cultural experiences. Cultural integration in learning is a study that offers a new perspective on how intercultural competence can be systematically built through pedagogical designs that are sensitive to the socio-cultural context of learners, as well as providing practical implications for the development of BIPA learning that is more adaptive, inclusive, and effective in improving cross-cultural communication success.